Characterization of gold nanoparticle suspensions in the presence of the poly (N-isopropylacrylamide) -co-poly (3-acrylamidopropyl trimethylammonium) copolymer. Influence of ionic strength and temperature - Herrera Robalino, David; Hernández Cifre, José Gines (ACI Avances en Ciencias e Ingenierías, 2021)
The coating of metallic nanoparticles with polymer is of interest to provide stability to the suspensions of said nanoparticles. On the other hand, there are thermosensitive polymers that respond according to the temperatures to which they are exposed.This study aimed to evaluate and characterize the system made up of gold nanoparticles and a version of the thermosensitive copolymer PNIPAAM-PAMPTMA (+) 48/6. For this, dynamic light scattering techniques, zeta potential and ultraviolet visible spectroscopy were used. PNIPAAM-PAMPTMA (+) 48/6 was subjected to tests at different temperatures in which it was confirmed that the lower critical dissolution temperature of the copolymer is approximately 35 oC and that in the presence of a saline medium it tends to add independently of the temperature. On the other hand, the copolymer was mixed with gold nanoparticles to study its behavior at ionic forces between 0 M and 0.75 M. It was found that, by varying the ionic strength in the mentioned range, the coating of the gold nanoparticles by part of the polymer is effective since no aggregation thereof was observed. This was corroborated by the UV-visible spectrum where, the spectra of the system (or nanocomposite) copolymer-nanoparticle at ionic strengths of 0 M and 0.75 M are practically equal to the spectrum when the gold nanoparticles have not added, that is to say , the plasmon peak appears in all cases at the same approximate wavelength of 530 nm. Finally, the evolution of the copolymer-nanoparticle system was studied at different temperatures and ionic forces of 0 M and 0.75 M. It was detected that both the influence of temperature and ionic strength cause the copolymer-nanoparticle system to increase its size. . However, the gold nanoparticles inside it remain without aggregating.
Keywords: gold nanoparticles; thermoresponsive copolymer; aggregation dynamic light scattering; zeta potential; UV-vis spectroscopy